Fermentation of wet-exploded corn stover for the production of volatile fatty acids. (March 2017) - Murali, Nanditha; Fernandez, Sebastian; Ahring, Birgitte Kiaer
Highlights: Volatile fatty acids (VFA) production was studied using rumen bacteria. Fermentation of pretreated corn stover to VFA. VFA yield increased to 40.8 g/L at 5% total solids (TS) from 22.8 g/L at 2.5% TS. Valeric acid production was seen only at 5% TS but not at 2.5% TS. Composition analysis showed 33% carbohydrates conversion at 2.5% and 50% at 5% TS. Abstract: Volatile fatty acids (VFA ) have been used as platform molecules for production of biofuels and bioproducts. In the current study, we examine the VFA production from wet-exploded corn stover through anaerobic fermentation using rumen bacteria. The total VFA yield (acetic acid equivalents) was found to increase from 22.8 g/L at 2.5% total solids (TS) to 40.8 g/L at 5% TS. It was found that the acetic acid concentration increased from 10 g/L to 22 g/L at 2.5% and 5% TS, respectively. An increased propionic acid production was seen between day 10 and 20 at 5% TS. Valeric acid (4 g/L) was produced at 5% TS and not at 2.5% TS. Composition analysis showed that 50% of the carbohydrates were converted to VFA at 5% TS and 33% at 2.5% TS. Our results show that rumen fermentation of lignocellulosic biomass after wet explosion can produce high concentrations ofVFA without addition of external enzymes of importance for the process economics of lignocellulosic biorefineries.